Performance of precast segmental concrete beams posttensioned with carbon fiber-reinforced polymer (CFRP) tendons - Le, Tan; Pham, Thong; Hao, Hong; Yuan, Cheng (Elsevier Ltd, 2019)
© 2018 Elsevier Ltd Precast segmental prestressed concrete beams (PSBs) have been widely used in many elevated highway bridge projects around the world. Steel tendons at joint locations, however, are vulnerable to corrosion damages, which cause deteriorations and in extreme cases lead to the collapse of the whole structures. This study experimentally investigates the use of carbon fibre-reinforced polymer (CFRP) tendons as an alternative solution for the PSBs to tackle the corrosion issue. Four large-scale segmental T-shaped concrete beams with internal bonded or unbonded tendons and dry or epoxied joints were built and tested under four-point loading. The test results indicated that CFRP tendons showed satisfactory performances therefore could replace steel tendons for the use in PSBs. All the tested beams exhibited excellent load-carrying capacity and ductility. Tendon bonding condition greatly affected the flexural performance of the segmental beams. Joint type had only a slight effect on the load-carrying capacity and ductility of the beams, but significantly affected the beams’ initial stiffness. Unbonded tendons experienced an evident reduction in the tendon strength at the ultimate stage as a consequence of the loading type, harping effect and joint opening. Both AASTHO-1999 and ACI 440.4R-04 predicted well the tendon stress, thus the load-carrying capacity of the beams with bonded tendons, however, the accuracy significantly reduced for the cases with unbonded tendons. Similarly, the codes did not well estimate the deformation capacity of the prestressed beams with unbonded tendons. An empirical formula is proposed to predict the deflections of beams with unbonded tendons, which yields very close predictions to the experimental results.